The Effect of Cigarettes on Schizophrenia Patients - Maylia, Mira Lovita; Azizah, Nur; Algristian, Hafid (Jurnal Medis Islam Internasional, 2024)
Introduction: The prevalence of smoking in patients with schizophrenia is still high around 70-80%. Although reports suggest that smoking increases the risk of developing schizophrenia, the potential role of smoking in this relationship requires further investigation. Smokers with schizophrenia were more likely to have more intense positive symptoms and lower cognitive function, but the intensity of extrapyramidal side effects was reduced compared to schizophrenic patients who were non-smokers. Objectives: The purpose of the study was to explain schizophrenia, dopamine, the etiology of cigarette use in patients with schizophrenia, the mechanism of action, the relationship between schizophrenia cases and cigarettes, the management of patients with schizophrenia and the relationship between the administration of antipsychotics to patients with schizophrenia and active smokers. Methods: This research journal uses a qualitative method, namely a descriptive research method and usually uses analysis. This research journal uses secondary data sources. The data collection method used is data derived from literature studies obtained from journals, books, and dissertations of Google Scholar and PubMed. The data collection tool used is documents. Results:  The nicotine in cigarettes interacts with nicotinic receptors in the brain, affecting the release of dopamine and serotonin. This can affect negative symptoms in schizophrenic patients, although the effect on positive symptoms still needs more research to be fully understood. Although the exact mechanism is not yet fully understood, some hypotheses indicate that smoking may play a role in managing negative symptoms and influencing impaired dopamine regulation in schizophrenia. Schizophrenia patients who are also active smokers face challenges in treatment with antipsychotics such as clozapine and olanzapine. Smoking can affect the metabolism of these drugs through the induction of the CYP1A2 enzyme, so it is necessary to adjust the dosage to maintain therapeutic efficacy. Appropriate adjustment of antipsychotic doses is necessary to optimize the management of schizophrenic symptoms without increasing the risk of unwanted side effects. Conclusion: In patients with schizophrenia the production of the neurotransmitter dopamine is excessive. When dopamine levels are unbalanced, excessive or reduced, sufferers can experience both positive and negative symptoms. Although smoking may provide some benefits in reducing negative symptoms in schizophrenia, the overall impact is still complex and requires more research. Future studies are expected to better understand the mechanism of interaction between smoking and schizophrenia and develop better treatment strategies.